The review of the crime of aggression commentaries - Turava, Merab; Dgebuadze, Giorgi (Journal of Law, 2019)
The paperwork is the review in Georgian language of the crime of aggression commentaries: Kreß Claus / Barriga, Stefan (ed.), Crime of Aggression Library, The Crime of Aggression: A Commentary, Vol. I&II (Cambridge University Press, 2017) 1583 pp. US$350.00 (Hardback) ISBN 9781107015265